Nature-Based Flood Risk Management on Private Land Disciplinary Perspectives on a Multidisciplinary Challenge - Hartmann, Thomas; Slavíková, Lenka; McCarthy, Simon (Springer Nature, 2019)
This open access book addresses the various disciplinary aspects of nature-based solutions in flood risk management on private land. In recent decades, water management has been moving towards nature-based solutions. These are assumed to be much more multi-purpose than traditional "grey infrastructures" and seem to be regarded as a panacea for many environmental issues. At the same time, such measures require more - and mostly privately owned - land and more diverse stakeholder involvement than traditional (grey) engineering approaches. They also present challenges related to different disciplines. Nature-based solutions for flood risk management not only require technical expertise, but also call for interdisciplinary insights from land-use planning, economics, property rights, sociology, landscape planning, ecology, hydrology, agriculture and other disciplines to address the challenges of implementing them. Ultimately, nature-based flood risk management is a multi-disciplinary endeavor. Featuring numerous case studies of nature-based flood risk management accompanied by commentaries, this book presents brief academic reflections from two different disciplinary perspectives that critically highlight which specific aspects are of significance, and as such, underscore the multi-disciplinary nature of the challenges faced. ;